KEANEKARAGAMAN DAN POTENSI PAKU (PTERIDOPHYTA) DI TAMAN NASIONAL GUNUNG GEDE PANGRANGO CIANJUR (TNGGP) - Syafrudin, Yudi; Haryani, Tri Saptari; Wiedarti, Sri (Fakultas Matematika dan ilmu pengetahuan Alam. Universitas Pakuan.)
The research Diversity and Potential paku (Pteridophyta) in The Taman Nasional Gede Pangrango Montain Cianjur have been done. Transek and plot sample method use in this research on three area of different altitude (1600, 1900, 2200 m above sea level). The result research show there were 56 species of ferns that include in 21 families. At an altitude of 1600 m above sea level diversity ferns include in the medium category with value 1,48, at an altitude of 1900 m above sea level diversity ferns include in the medium category with value 1,02, and altitude of 2200 m above sea level diversity ferns include in the low category with value 0,93. Ferns in the TNGGP have potensial for the surroundings communities Kebun Raya Cibodas. Key words : Ferns, diversity, Gede Pangrango Mountain.